Clean energy and the fragile supply chain: lessons from U.S.-China trade tensions and energy shocks - Si Mohammed, Kamel; Radulescu, Magdalena; khalfa Brika, Said; Popescu, Luigi; Barbulescu, Marinela (Frontiers in Environmental Science, 2025)
IntroductionThis study explores the time-varying connectedness and spillover transmission among supply chain disruptions in China, clean energy technology, energy prices (BRENT), U.S.–China trade tensions (UCT), and economic policy uncertainty (EPU). Understanding these interdependencies is crucial for assessing how shocks propagate across economic and environmental systems.MethodsUsing quarterly data from 2006 to 2024, the analysis employs the Time-Varying Parameter Vector Autoregression (TVP-VAR) and Quantile VAR (QVAR) approaches. These models capture both dynamic and distribution-dependent spillover effects across markets and policy variables.ResultsFindings indicate that Chinese supply chain disruptions act as the primary net transmitter of shocks, especially during crises such as COVID-19, trade conflict escalations, and the recent global energy shock in the Red Sea region. After 2020, climate technology emerges as a more influential transmitter in high-quantile regimes, while BRENT and UCT alternate their roles across quantiles. Robustness tests using network-based quantile analysis confirm the nonlinear and state-dependent characteristics of these spillover effects.DiscussionThe results provide new insights into how domestic disruptions in China’s carbon-intensive supply chains reverberate through broader environmental, economic, and policy systems. The study offers essential implications for resilience planning, sustainable technology.